Behaviour of antelopes around perenialwaterholes in Kainji lake national park (KLNP),Nigeria (2013)
Mammals spend more time around available water points especially during the dry season. This makes waterholes strategic spots for close observation of animals behavior. This study assessed the seasonal distribution of selected antelopes (Hippotragus equinus , Kobus kob, and Silvicapral grimmia) in KLNP, with a view to examining their daily activities and common behaviors . The study involved direct observation and identification of the selected antelopes around three perennial waterholes (Rivers Kpesa, Nanon and Oli) 10 - 24 km apart, from high hides. The indirect method on the other hand involved establishment of three 10m2 quadrants in each of the three study waterholes for observation of the Antelopes activities and interactions. This was done from 6am 6pm for six consecutive days monthly from July, 2011 to June, 2013. Data obtained were analyzed using descriptive statistics. From the study, Kobus kob had the highest percentage of observation in the study area (62.8%) followed by Hipptragus equinus (20.4%) and silvicapral grimmia (16.8%). The average herd size was 9 for Kobus kob, 5 for Hipptragus equinus and 1 for Silvicapral grimmia. Animals in herds stay longer at the waterhole than the solitary duiker. Peak periods for maximum observation of antelopes around the water holes are 8.00-10.00hrs and 16.00-18.00hrs for Kobus kob and Silvicapral grimmia while that of Hippotragus equinus is 11.00-13.00hrs of the day. . Understanding of basic behavioral pattern of mammals will contribute in no small way to their effective management. A good timing of game viewing will increase the chances of antelope encounter in shortest period of tour.